Preparation and application of low-temperature-curable, alkylphenol ethoxylate-free, and flame-retardant flocking adhesive. Issue 6 (3rd June 2019) - Wu, Haiting; Jiang, Xiaojuan; Cai, Zaisheng
Abstract: In this study, a low temperature-curable and alkylphenol ethoxylate-free acrylic emulsion was synthesized with diacetone acrylamide (DAAM) and adipic dihydrazide (ADH) as a crosslinking system; butyl acrylate (BA), ethyl acrylate (EA), methyl methacrylate (MMA), and acrylic acid (AA) as monomers; vinyl siloxane as a modifier; sodium-dodecyl sulphate (SDS) and AEO-9 as a compound emulsifier by means of semicontinuous emulsion polymerization. The optimal polymerization conditions by weight proportion determined by the orthogonal experiments were emulsifier amount, 4%, initiator amount, 0.5%, DAAM amount, 2.5%, and core–shell ratio, 3/2. Three flame-retardant additives, namely, ammonium polyphosphate (APP), FR-5, and organic montmorillonite, were mixed with the acrylic emulsion to synthesize the flocking adhesive SA. The char length, afterglow time, and afterflame time of the flocking fabrics were characterized to evaluate the fire-retardant properties of the adhesives. The results clearly evidence an outstanding improvement in fire-retardant properties using adhesive SA based on good flocking fastness and fabric handle.